2015
DOI: 10.1002/rcr2.143
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy with hypoplastic left lung complicated by pneumothorax and pulmonary embolism

Abstract: We report a case of a 34‐year‐old lady with past history of asthma and pulmonary tuberculosis, who presented 5 weeks pregnant with acute dyspnea. Her chest X‐ray showed left‐sided complete lung collapse and concomitant right‐sided pneumothorax. The pneumothorax was initially managed conservatively with a chest tube but due to its persistence despite suction, was subsequently changed to a PneumostatTM, with which she was later discharged. She had a normal echocardiography (ejection fraction [EF] 67%) at 5 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…c On the day before cesarean section, chest X-ray in supine position confirmed no significant displacement of the diaphragm, when considering the impact of the posture on diaphragm position; however, it revealed further increase of vascular shadows in the right lung field. d No abnormal findings in the lung field and no significant change of the diaphragm level, compared with those the day before the operation, were confirmed, immediately after the cesarean section ventilation [4,6,7]. Muammer et al reported that spinal anesthesia (SA) for cesarean section had no negative effects, on both FVC and FEV 1.0 , even in a woman with CF, who had severely impaired pulmonary function [7].…”
Section: Discussionmentioning
confidence: 96%
“…c On the day before cesarean section, chest X-ray in supine position confirmed no significant displacement of the diaphragm, when considering the impact of the posture on diaphragm position; however, it revealed further increase of vascular shadows in the right lung field. d No abnormal findings in the lung field and no significant change of the diaphragm level, compared with those the day before the operation, were confirmed, immediately after the cesarean section ventilation [4,6,7]. Muammer et al reported that spinal anesthesia (SA) for cesarean section had no negative effects, on both FVC and FEV 1.0 , even in a woman with CF, who had severely impaired pulmonary function [7].…”
Section: Discussionmentioning
confidence: 96%